"Semanario Pintoresco Español" (1836-1857): News about Galician Culture on the Romantic Press in the Centre of the Peninsula - Navas Sánchez-Élez, María Victoria (Madrygal. Revista de Estudios Gallegos, 2015)
An analysis of the Semanario Pintoresco Español (1836-1857), a periodical and miscellaneous Castilian publication, which will reveal its numerous references to Galician culture presented from its Iberian 19th century viewpoint.